Rancang Bangun Alat Blanket Warmer Berbasis Arduino Uno dengan Menggunakan Sensor DS18B20 - M. Qi Bagus Maulana; Septi Aprilia; Eko Nugroho; Ida Untari (Pusat Riset dan Inovasi Nasional, 2024)
Blanket warmer is a tool to maintain the stability of the patient's body temperature when experiencing hypothermia, the blanket warmer will warm the patient until it reaches a normal body temperature of 36 - 37 °C. Some of the temperature setting options on the blanket warmer are 32°C, 38°C, and 43°C. To be able to design an Arduino-Based Warmer Blanket tool by using DS18B20 sensors.This study uses the research and development (RnD) method, which is a method used to make a product and test its effectiveness from the results of the product. The results of this study had a measurement difference of the instrument that could be used for patients with the highest temperature difference, namely 32°C = 0.11°C, 38°C = 0.20°C, 43°C = 0.11°C, the lowest measurement difference was 32°C = 0°C, 38°C = 0.01°C, 43°C = 0.02°C by comparing with a temperature measuring instrument. The average of all measurements in patients was 32°C = 32.64°C, 38°C = 38.70°C, 43°C = 43.72°C. The highest average error value from the 3 experiments was 1.45% and the lowest average error value from the 3 experiments was 0.26%. The Blanket Warmer tool using sensors DS18B20 safe for patients to use.